The participation of indigenous community leaders in marriage based on Law No. 1 of 1974 concerning Marriage - Gatot Efrianto; Arovah Windiani (PT Publikasiku Academic Solution, 2023)
In each region, of course, there is a diversity of customs that apply in the indigenous people of an area, one of which is regarding marriages carried out customarily. Customary marriage is an important and sacred event for indigenous peoples, to live together as husband and wife with the aim of realizing the unity of a happy and eternal home, in which there is a great responsibility not only to the integrity of their household but also to the environment, society and also God. Regarding the issue of Indonesian customary law, it is very principled because adat is one of the mirrors for the nation, adat is an identity for the nation, and identity for each region. Indonesia is a country that adheres to plurality in the field of law, where the existence of western law, religious law and customary law is recognized. This research study is juridical normative as the main approach, considering that the discussion is based on laws and legal principles that apply in customary marriage issues. The Participation of Indigenous Peoples' Leaders in Marriage Of course, the community can maintain and preserve the culture of local wisdom and the values contained therein because the birth of Law Number 1 of 1974 concerning Marriage is a law that is a manifestation of many customary laws, ethnic groups in Indonesia that have privileges, which regulate all members of society who have reached adulthood who will carry out marriage